The Effect of Zeolite and Palm Kernel Cake (Pkc) On Fecal Ammonia Production and House Fly Population - Wihandoyo (2000)
Four experiments were conducted to evaluate the effect of zeolite and Palm Kernel Cake (PKC) on ammonia production and house fly Musca domestica L population. In the first experiment, three periods of manure removal (every 30, 20 and 10 days or MR3, MR2 and MRI) with two cage densities (single and double birds or CDI and CD2) were carried out. The low cage density and frequent manure removal decreased significantly (P<O.O I) the ammonia (NH3) production by the feces and fly larvae population in the manure, but had no effect on layer performance. In the second experiment, three levels of zeolite (0, 6 and 12% ZD) in the diet and three levels of zeolite spread directly on the manure (0, 6 and 12% ZS of total daily feed intake) were tested. Incorporation of high levels of zeolite in the diets and zeolite spread on the manure decreased significantly (P<O.OI) the fly larvae population, NH3 production, water, pH, CP, Ca and P contents of manure. Incorporation of high levels of zeolite in the diets affected the FCR, HDA and shell thickness, but did not influence chemical content of both egg albumen and yolk. Dietary zeolite also had no significant affect on tibial length, weight, Ca and P content. In the third experiment, three levels of zeolite (0, 6 and 12%) and four levels of PKC (0, 12, 24 and 36%) were incorporated in the layer diets. Incorporation of high levels of PKC and zeolite decreased significantly (P<0.01) the fly larvae population, NH3 production, fecal water content, and Ca, P and CP of the feces. Incorporation of high levels of PKC and zeolite significantly (P<O.OI) increased Fl, FCR HU, eggshell weight and thickness but decreased HDA. Crude protein and Ca of egg albumen and yolk contents increased in accordance with increasing levels of zeolite and PKC in the diets. The increasing levels of zeolite improved Ca but decreased the P content of egg shell, while the levels of PKC decreased shell Ca and P. Incorporation of high levels of PKC and zeolite in the layer diets increased the tibia and femur length but decreased tibial Ca and P contents. Increasing levels of PKC and zeolite in the layer diets increased Ca, P and cholesterol contents of blood plasma. In the fourth experiment, three levels of zeolite (0, 1 and 2%) and three levels of PKC (0, 15 and 30%) were incorporated in the broiler diets. Incorporation of high levels of PKC and zeolite in the broiler diets reduced broiler performance (Fl, body weight, carcass percentage and FCR). Increasing levels of zeolite significantly (P<0.05) decreased the cholesterol, Ca and P contents of blood plasma, Incorporation of high levels of PKC and zeolite were able to reduce NH3, number of fly larvae and water content of manure. Palm kernel cake and zeolite could be used as a poultry feedstuff or a feed additive and zeolite was able to assist in reducing the ammonia production and house fly larvae population in the poultry feces.